Prognostic impact of insomnia in patients receiving trans-catheter aortic valve replacement - Imamura, Teruhiko; Ushijima, Ryuichi; Sobajima, Mitsuo; Fukuda, Nobuyuki; Ueno, Hiroshi; Kinugawa, Koichiro (Journal of cardiology, 2024)
The presence of insomnia exhibits a profound association with diverse cardiovascular pathologies. However, its prognostic implications in patients undergoing transcatheter aortic valve replacement (TAVR) for severe aortic stenosis remain ambiguous. This retrospective study enrolled patients who underwent TAVR for severe aortic stenosis at a prominent academic center from 2015 to 2022. The impact of insomnia, operationally defined as the prescription of soporific agents, on the two-year composite primary outcome comprising all-cause mortality and hospital readmissions was scrutinized. A cohort of 345 patients (median age 85 years, 99 males) was encompassed in the analysis. All subjects underwent successful TAVR and subsequent discharge. The presence of insomnia (N = 91) emerged as an independent predictor of the two-year composite endpoint, with an adjusted hazard ratio of 1.66 (95 % confidence interval 1.08–2.57, p = 0.022), significantly delineating the two-year cumulative incidence of the primary endpoint (40 % versus 30 %, p = 0.035). Approximately one-fourth of TAVR candidates manifested symptoms of insomnia, a condition autonomously correlated with heightened mortality and morbidity following the TAVR procedure. The optimal strategy for addressing insomnia in TAVR candidates constitutes a paramount consideration for future interventions. [Display omitted] •One-fourth of transcatheter aortic valve replacement (TAVR) candidates had insomnia.•Insomnia was an independent predictor for death or readmission after TAVR.•Type of sleep medicine did not affect post-TAVR clinical outcome.